P‐71: A 3D/2D Convertible Integral Imaging Display with High Optical Efficiency. Issue 1 (June 2015) - Deng, Huan; Wang, Qiong‐Hua; Li, Da‐Hai; Luo, Cheng‐Gao
Abstract : We propose a method for highopticalefficiency three‐dimensional (3D)/ two‐dimensional (2D) convertible integral imaging display. A reflective polarizer can reflect the polarized light which is orthogonal to the transmission axis of the reflective polarizer and transmit the polarized light which is paralleled to the transmission axis of the reflective polarizer. The reflected light can be recycled because of the depolarization property of the diffuser, sothe optical efficienciesfor both 3D and 2D display modesare enhanced. 3D display mode is realized byadopting a pinhole array on a polarizer to generate point light source array. 3D/2D convertible feature is realized by electrically controlling the polarization switcher. In the experiments, the 3D/2D conversion and the improvement of the optical efficiency are demonstrated.